2023
DOI: 10.1108/tlo-08-2022-0097
|View full text |Cite
|
Sign up to set email alerts
|

The future of work: work engagement and job performance in the hybrid workplace

Abstract: Purpose Drawing on the job demands-resources (JD-R) model, the authors examine how working in the hybrid workplace model (telework and flexible work) affects job performance via the intervening role of work engagement. Design/methodology/approach The authors adopted a quantitative approach and collected data from 277 employees working in universities in Nigeria. Partial least square structural equation modelling was used to analyse the data and test the hypotheses. Findings The findings reveal that flexibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…These results can be compared with the findings of Naqshbandi et al (2024), who investigated the effects of the telework on the work performance of college employees in Nigeria. They found no positive effects of telecommuting on employee productivity.…”
Section: Can Teamwork Thrive In the Hybrid Workplace?mentioning
confidence: 93%
See 2 more Smart Citations
“…These results can be compared with the findings of Naqshbandi et al (2024), who investigated the effects of the telework on the work performance of college employees in Nigeria. They found no positive effects of telecommuting on employee productivity.…”
Section: Can Teamwork Thrive In the Hybrid Workplace?mentioning
confidence: 93%
“…-Saving on fuel costs; and -Saving on living costs. Naqshbandi et al (2024) studied the effects of teleworking on the work performance of college employees in Nigeria and also found that flexible working arrangements allow for greater time autonomy and promote work performance. Some employees perform better in the morning, while others prefer later working hours.…”
Section: Challenges Of Developing a Learning Culturementioning
confidence: 99%
See 1 more Smart Citation
“…This relationship goes beyond physical comfort and encompasses psychological and cognitive aspects that profoundly influence how employees carry out their tasks and contribute to the organization's objectives [16]. Job performance is no longer viewed as a standalone measure but rather as a complex outcome influenced by multiple factors, including work engagement and talent retention [17,18]. Work engagement plays a vital role in connecting ergonomics with job performance.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid work has become a feature of the era after Covid-19 (Nenonen & Sankari, 2022;Aoyama & Silva, 2023;Oygür et al, 2022;Petani & Mengis, 2021;Surma et al, 2021;Hopkins & Bardoel, 2023;Borg & O'Sullivan, 2021). For instance, according to a McKinsey survey conducted in early 2021, it stated that in a post-pandemic world, 20% to 25% of workers in industrialized nations could work remotely (Hirsch, 2021;Naqshbandi et al, 2023). There seems to be a subset of employees that are not prepared to resume their regular pre-pandemic employment (Wang et al, 2023;John et al, 2023).…”
Section: Introductionmentioning
confidence: 99%